Genomic capacities for Reactive Oxygen Species metabolism across marine phytoplankton - Omar, Naaman M; Fleury, Katherine; Beardsall, Brian; Prášil, Ondřej; Campbell, Douglas A (PloS one, 2023)
Marine phytoplankton produce and scavenge Reactive Oxygen Species, to support cellular processes, while limiting damaging reactions. Some prokaryotic picophytoplankton have, however, lost all genes encoding scavenging of hydrogen peroxide. Such losses of metabolic function can only apply to Reactive Oxygen Species which potentially traverse the cell membrane outwards, before provoking damaging intracellular reactions. We hypothesized that cell radius influences which elements of Reactive Oxygen Species metabolism are partially or fully dispensable from a cell. We therefore investigated genomes and transcriptomes from diverse marine eukaryotic phytoplankton, ranging from 0.4 to 44 μm radius, to analyze the genomic allocations encoding enzymes metabolizing Reactive Oxygen Species. Superoxide has high reactivity, short lifetimes and limited membrane permeability. Genes encoding superoxide scavenging are ubiquitous across phytoplankton, but the fractional gene allocation decreased with increasing cell radius, consistent with a nearly fixed set of core genes for scavenging superoxide pools. Hydrogen peroxide has lower reactivity, longer intracellular and extracellular lifetimes and readily crosses cell membranes. Genomic allocations to both hydrogen peroxide production and scavenging decrease with increasing cell radius. Nitric Oxide has low reactivity, long intracellular and extracellular lifetimes and readily crosses cell membranes. Neither Nitric Oxide production nor scavenging genomic allocations changed with increasing cell radius. Many taxa, however, lack the genomic capacity for nitric oxide production or scavenging. The probability of presence of capacity to produce nitric oxide decreases with increasing cell size, and is influenced by flagella and colony formation. In contrast, the probability of presence of capacity to scavenge nitric oxide increases with increasing cell size, and is again influenced by flagella and colony formation.
Keywords: Nitric Oxide; Reactive Oxygen Species; Phytoplankton; fytoplankton; peroxid vodíku; oxid dusnatý; Superoxides; superoxidy; Hydrogen Peroxide; Genomics; reaktivní formy kyslíku; genomika